Oreocharis curvituba, a new species of Gesneriaceae from northeastern Guangxi, China - Wei, Jiajia; Xiong, Guochun; Zou, Chunyu; Pan, Bo; Xu, Weibin (Phytotaxa, 2016)
Oreocharis curvituba, a new species of Gesneriaceae from Guangxi, China, is described and illustrated. It resembles O. stenosiphon and O. magnidens in the leaf characters, but it differs from the latter by its corolla with tube slightly curved, marked with purple star and a ring of glandular hairs at mouth.